PENGEMBANGAN MEDIA KARTU Q&A BERBASIS MODEL MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS IV DI SDN 105328 DAGANG KERAWAN TAHUN AJARAN 2023/2024 - Latifah Utami Siregar; Wildansyah Lubis; Halimatusakdiah; Faisal; Winara (STKIP Subang, 2025)
This research was conducted to determine how to develop Q&A card media based on the Make a Match model and also to determine the effectiveness and feasibility of the card in increasing student activeness in learning Indonesian in grade IV of SDN 105328 Dagang Kerawan. This research is a development research (R&D) conducted using the ADDIE development procedure. To assess the feasibility and effectiveness of the developed media, a validation questionnaire was used which was given to the media expert validator and also the grade IV teacher of SDN 105328 Dagang Kerawan. From the results of the study, it was known that the feasibility score obtained from the media expert validator was 90 with the criteria of